The effect of speed humps on pavement conditions in local streets - Nurshahana, Yusof Shah (2019)
Speed humps is one of the traffic calming devices beside speed bumps, speed tables, roundabouts, transverse rumble strips, optical speed bars, textured pavement, and cat-eye reflectors. Main function of these devices is to control and calm the speed of vehicles such as cars, lorries and motorcycles so that they were driven at suitable speed, through critical areas or local streets. It also can be acknowledged as a raised pavement which is spanning across roadway to force drivers to reduce the speed of their vehicles. By slowing down their vehicles, more time could be given to the pedestrians to safely cross the road. The objective of this research is to identify surface pavements conditions within speed humps area and to determine the most suitable type of road hump to be build based on the traffic volumes at the study area. In order to achieve the objectives, traffic counting were carried out during peak hours at 5 speed humps along Sri Damai Road (C181). The traffic volume for this study area is in range of 2,000-5,000 vehicles per day. From this study, it was found out that the size and characteristics of hump located at the study area are totally different than Public Work Department’s standard specification in terms of height and length of hump. The best speed hump that is suitable to be used at this local road is sinusoidal with 4 meter in length and 100 mm of height. The defect that usually occur before and after the hump is crocodile crack, transverse crack, block cracking, pothole and depression by divided it into three main conditions which is less severe, medium severe and badly severe. It is hope that there outcomes from this thesis could help the Public Work Department to plan appropriate measure for surface improvement at humps located at local roads.